Modelling the potential prevention benefits of a treat‐all hepatitis C treatment strategy at global, regional and country levels: A modelling study. Issue 12 (30th August 2019) - Trickey, Adam; Fraser, Hannah; Lim, Aaron G.; Walker, Josephine G.; Peacock, Amy; Colledge, Samantha; Leung, Janni; Grebely, Jason; Larney, Sarah; Martin, Natasha K.; Degenhardt, Louisa; Hickman, Matthew; et al.
Abstract: The World Health Organization (WHO) recently produced guidelines advising a treat‐all policy for HCV to encourage widespread treatment scale‐up for achieving HCV elimination. We modelled the prevention impact achieved (HCV infections averted [IA]) from initiating this policy compared with treating different subgroups at country, regional and global levels. We assessed what country‐level factors affect impact. A dynamic, deterministic HCV transmission model was calibrated to data from global systematic reviews and UN data sets to simulate country‐level HCV epidemics with ongoing levels of treatment. For each country, the model projected the prevention impact (in HCV IA per treatment undertaken) of initiating four treatment strategies; either selected randomly (treat‐all) or targeted among people who inject drugs (PWID), people aged ≥35, or those with cirrhosis. The IA was assessed over 20 years. Linear regression was used to identify associations between IA per treatment and demographic factors. Eighty‐eight countries (85% of the global population) were modelled. Globally, the model estimated 0.35 (95% credibility interval [95%CrI]: 0.16‐0.61) IA over 20 years for every randomly allocated treatment, 0.30 (95%CrI: 0.12‐0.53) from treating those aged ≥35 and 0.28 (95%CrI: 0.12‐0.49) for those with cirrhosis. Globally, treating PWID achieved 1.27 (95%CrI: 0.68‐2.04) IA per treatment. The IA per randomly allocated treatment was positively associated with a country's population growth rate and negatively associated with higher HCV prevalence among PWID. In conclusion, appreciable prevention benefits could be achieved from WHO's treat‐all strategy, although greater benefits per treatment can be achieved through targeting PWID. Higher impact will be achieved in countries with high population growth.